UJI COBA UMPAN BUAH SAWIT PADA PENANGKAPAN IKAN LIMBAT (Clarias niehofii) DI RAWA DESA SUKAMAJU KABUPATEN TEBO-JAMBI - Muhammad Natsir Kholis; La Ode Wahidin; Yudha Maulana Syuhada (LPPM Universitas Bina Insan, 2020)
A fish trap becoming one of fishing gears commonly utilized to catch fish in swamps and rivers in Jambi. Using this kind of gears is frequently accompanied by baits to interest the target fish to getting in this trap. This research was aimed at testing the fruits of oil-palm as baits in capturing the slender walking catfish (Clarias nieuhofiii) in Tebo Regency, Jambi. Collecting data was carried out for three months starting from June to August 2020 in the swamp waters of Sukamaju Village, Rimbo Ulu Sub-district, Tebo Regency – Jambi. The method used was a survey by applying an experimental fishing. Amounts of three wire traps accompanied with oil-palm fruits as baits had been applied to catch the fish with 30 times of replications. The catch fish were identified, tabulated and analysed. The results of this research indicate about the 145 fish captured using the fishing gear are dominated by the slender walking catfish (C. niehofii), followed by four other fish species such as three spot gourami (Trigchogaster trichopterus), forest snakehead fish (Channa lucius cuvier), climbing perch (Anabas testudineus), and (crab) yuyu (Parathelphusa convexa). The highest and lowest catch occur on July and June, respectively. The catch slender walking catfish possesses size variations such as length range of 8.70 cm – 38.00 cm (in average of 19.27 cm), and weight range of 8.90 grams – 213.60 grams (in average of 73.33 grams). The utilization of oil-palm plant fruits as baits of wire-traps is able to attract the target fish into the applied traps.bait